Os rastros mnêmicos e intermidiáticos de Ofélia em ELENA, de Petra Costa - Lorena Cristiane de Souza Camilo (2023)
For years, literature has been a source of inspiration for various artists from different types of art. Supported by filmmaker Petra Costa's statement regarding the influence of the character Ophelia – not only from the theatrical play Hamlet (1599-1601) but also as depicted in the paintings titled Ophelia by John Everett Millais (1851-1852) and John William Waterhouse (1889), as well as in Gustav Klimt's painting The Virgin (1913) – in the creation of her feature film ELENA (2012), the present research aims to analyze the presence and influences of these media in the film. To accomplish this, this dissertation draws upon Intermediality Studies, primarily relying on the concepts of media transposition and intermedial reference coined by Irina O. Rajewsky (2012). Considering that analyses of Ophelia's image reveal that the portrayal of the character has not changed over the years, from the Elizabethan era to contemporary times, being seen as the archetype of the melancholic, hysterical, and dead character in the various media transpositions that have been made, the objective of this dissertation is to demonstrate that Petra Costa, in her narrative and visual construction in the film ELENA, employs Ophelia's death with the purpose of resignifying it.